SELF-HYPNOSIS USING BOOKLET ON ANXIETY IN THIRD TRIMESTER PREGNANCY - Zetira Salsa Herawati; Yulifah Salistia Budi; Nuristy Brillian Ainindyahsari Winarna (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Background: Anxiety during pregnancy is a negative emotional state caused by feelings of fear, worry, or restlessness related to various aspects of pregnancy. Self- hypnosis, delivered through a booklet, helps pregnant women achieve a calmer mental state, allowing them to manage anxious thoughts. This study aims to assess the effectiveness of self-hypnosis with a booklet on anxiety during the third trimester. Method: The research design used is a quasi-experimental pretest- posttest with a control group using consecutive sampling. The study subjects comprised 60 pregnant women in the third trimester, divided into 30 women in the intervention group and 30 women in the control group. The intervention was conducted eight times a month for 30 minutes, using the PASS questionnaire. Result: The statistical test results using the paired T-test for pretest and posttest in each group showed p<0.05, meaning that there was significant effectiveness in the intervention group after being given self-hypnosis using a booklet. the majority of respondents answered statement 4 “Worry about many things” with a frequency of “often” to “sometimes” and statement 12 “Wanting things to be perfect” with a frequency of ‘always’ to “sometimes.” Meanwhile, in the control group, the majority of respondents answered statement 4 “Worry about many things” with a frequency of “often” to “always” and statement 12 “Wanting things to be perfect” with a frequency of ‘always’ remained “always”. Conclusion: Self-hypnosis using a booklet can be used as a non-pharmacological alternative to reduce anxiety in pregnant women. Midwives can apply this method.